2004
DOI: 10.1097/00126334-200408150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Validated Measures of Adherence Indicate High Levels of Adherence to Generic HIV Antiretroviral Therapy in a Resource-Limited Setting

Abstract: This sample of patients purchasing generic HIV antiretroviral therapy has among the highest measured adherence reported to date. Patient-reported measures were closely associated with objective measures. The relative ease of administration of the 30-day visual analog scale suggests that this may be the preferred method to assess adherence in resource-poor settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
214
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(234 citation statements)
references
References 17 publications
18
214
2
Order By: Relevance
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
“…Three measures of adherence were used: unannounced pill counts, 3-day self report and a 30-day visual analogue scale as previously described (Oyugi et al 2004). Adherence measures were collected monthly for patients initiating therapy and once for patients on stable antiretroviral therapy.…”
Section: Adherence Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…While the best method for assessing adherence in busy African ART clinics has yet to be defined [20,30-32], careful assessment and support for 100% adherence is a very important and affordable tool in the optimization of viral response to ART. Recent poor adherence must be addressed before switching patients in RLS to more complicated and costly regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence was measured by self report, using a modified Adult AIDS Clinical Trials Group adherence questionnaire validated in our setting [19,20]. Participants were asked to report adherence patterns in the three days prior to enrolment, four weeks prior to enrolment, and since the initiation of ART.…”
Section: Methodsmentioning
confidence: 99%